2015
DOI: 10.1093/carcin/bgv121
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between long and heterogeneous telomere length in blood lymphocytes and bladder cancer risk in Egyptian

Abstract: Although it is widely recognized that telomere dysfunction plays an important role in cancer, the relationship between telomere function and bladder cancer risk is not well defined. In a case-control study of bladder cancer in Egypt, we examined relationships between two telomere features and bladder cancer risk. Telomere fluorescent in situ hybridization was used to measure telomere features using short-term cultured blood lymphocytes. Logistic regression was used to estimate the strength of association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Telomere dysfunction is described to be associated with tumorigenesis across various cancers [13][14][15][16][17][18][19] and short telomeres may favor genomic instability, checkpoint deregulation, and activation of telomerase, leading to malignant transformation [12]. Different treatment strategies exploit the crucial role of telomere dysfunction, and targeting telomerase dependence of cancers shows promising impact in clinical trials [20].…”
Section: Introductionmentioning
confidence: 99%
“…Telomere dysfunction is described to be associated with tumorigenesis across various cancers [13][14][15][16][17][18][19] and short telomeres may favor genomic instability, checkpoint deregulation, and activation of telomerase, leading to malignant transformation [12]. Different treatment strategies exploit the crucial role of telomere dysfunction, and targeting telomerase dependence of cancers shows promising impact in clinical trials [20].…”
Section: Introductionmentioning
confidence: 99%
“…So far, only three studies have investigated circulating LTL and risk of pancreatic cancer [12, 28, 29], while none of them were conducted in Asians. Additionally, recent studies also showed that telomere length variation (TLV) across all chromosomal ends, which could increase chromosome instability and poor clinical outcome, contributed to the risk of bladder cancer [30]. To further clarify the association between LTL, TLV and pancreatic cancer and CRC development, we performed this nested case-control study to examine the degree of association between LTL, TLV and risk of pancreatic cancer and CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Telomere length deformities are universal in preinvasive stages of Carcinogenesis in human epithelial cells. Certainly, telomere shortening occurs mostly in early stage of bladder, colon, cervix, esophageal and oral cavity cancer [75,76]. This phenomenon is also observed in prostate cancer [77][78][79].…”
Section: Telomere Length In Multistep Carcinogenesismentioning
confidence: 99%